Cognitive Analysis of Product Form Elements - Shutao Zhang; Jianning Su; Chibing Hu; Peng Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Perception is the most basic form of cognition thinking activity. Consumers' perception image to the product form is based on human's visual perception characteristics, which can be summarized as the overall organization, the constant memory, the simple regulating and the identifiable discrimination according to the Gestalt principle. Firstly, the study analyzes the characteristics of consumers' perception image to the product form. Secondly, the evaluation model that is used to simulate consumers' image perceived behavior is build using gray correlation analysis and fuzzy neural network. Finally, the practice example of car side profile design is taken, and the results show that the method is helpful to product form image intelligent design.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3696